Impact of coherent and incoherent twin boundaries on the microhardness of annealed nanocrystalline Ni–W alloys. (3rd October 2017) - Lagarde, M.; Shakibi Nia, N.; Bourgon, J.; Conforto, E.; Creus, J.; Feaugas, X.; Savall, C.
Abstract: The microstructural evolution of nanocrystalline Ni–W alloys with annealing temperature and more specifically grain boundary (GB) character is investigated through several techniques and correlated with the hardening behaviour. It is shown that two distinct regions can be identified in relation to the annealing temperature and the microstructural evolution. At temperatures below 550 °C (Regime I), a small increase in grain size is observed and is accompanied by a significant hardening and an increase in the fraction of Σ3 incoherent twin boundaries. At temperatures above 550 °C (Regime II), the thermal stability is overcome and important grain growth occurs with a decrease in both the volumic fraction of GBs and the microhardness. It is suggested that the microhardness evolution during heat treatment is influenced by two opposing processes: an increase in the fraction of incoherent twin boundaries (hardening effect) and grain growth (softening effect). Both aspects are directly associated with the mean free path of mobile dislocations.